Influências do ângulo de corte e da anisotropia nas propriedades magnéticas dos aços elétricos o efeito textura - Santos, Julio Penin (2005)
The present thesis aims firstly to argue theoretically, of what occurs in carbon steel and silicon steel plates for electric ends, when used in transformers, electric motors and generators, and other electromagnetic devices. Secondly, experimental data and results are used to justify the "new" concepts adopted the analyses and conclusions drawn with samples of these materials. The total losses in the iron and the magnetic permeability, important in the choice of plates, are investigated taking in consideration their main function of magnetic flow amplifyers, and, therefore, more representative values are searched. For the fact of the measurement currently to be effected in the Epstein square with 50/50 values (0° and 90°), is considered, remaining the same device, to change themselves in plate GNO, for 25/50/25 (0°, 45° and 90°) with the proven certainty, gotten experimentally, that these values reflect more adequately what it occurs with plates mounted in the stators of engines of induction and alternating chain generators. In one of the studied samples, the difference between the two methods reaches 86,2% in the relative permeability, and 4,4% for the total losses in the iron, with B = 1,5 T, concluding itself for the immediate necessity of the change in the assay methodology.